Precursor Concentration and Substrate Effects on High Rate Dip-Coated Vanadium Oxide Thin Films. (10th February 2015) - Glynn, Colm; Aureau, Damien; O'Hanlon, Sally; Daly, Luke; Geaney, Hugh; Collins, Gillian; Etcheberry, Arnaud; O'Dwyer, Colm
Abstract : Uniform thin films of vanadium pentoxide were dip-coated from a high-concentration vanadium oxytriisopropoxide precursor which is shown to be resistant to the dewetting processes which can form surface pinhole defects. Through appropriate withdrawal speed choice, the thin films have a smooth uniform surface morphology with a low rms roughness of <1 nm in both their amorphous and crystallized states. The structure of the thin films follows that of bulk vanadium pentoxide but in a nanostructured form. The deposition methods shown can be applied to prepare thin films upon a variety of different substrates and other alkoxide based metal oxide materials.